In-hospital blood collection increases the rate of indeterminate results in interferon-gamma release assays. (February 2022) - Osakabe, Yuki; Yamaguchi, Fumihiro; Suzuki, Ayako; Kitano, Haruka; Hiraiwa, Mina; Shiratori, Yo; Onozaki, Shota; Nakamoto, Mari; Kawamura, Saori; Kosuge, Miku; Atarashi, Kenji; Cho, Hidekazu; et al.
Background: The interferon (IFN)-γ release assay (IGRA) has recently been established as a method to evaluate the infection status of tuberculosis instead of the tuberculin skin test. However, indeterminate results can create challenges to interpretation. The IGRA has been available in Japan since 2005, including the recently launched QuantiFERON-TB Gold Plus (QFT-plus) assay. Objectives: The aim of this study was to investigate the clinical features and predictors of indeterminate results by the QFT-plus test in routine practice. Methods: This was a cross-sectional study of 1258 patients. Multivariate logistic regression models were employed to investigate the clinical factors related to indeterminate results by the QFT-plus. Results: Overall, 91.8% of results were found to be conclusive and 8.2% were indeterminate. The QFT-plus indeterminate results were predominantly due to a low level of IFN-γ production by mitogens. Multivariate analysis indicated that an indeterminate result was significantly associated with age, sex, corticosteroid use, autoimmune disease, and inpatient setting. Conclusion: Certain types of individuals are at higher risk of an indeterminate IGRA result. The QFT-plus test for hospitalized patients should be avoided as much as possible, and it is better to perform the test for those patients in outpatient settings.